2004
DOI: 10.1074/jbc.m407243200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-phosphorylated and Nonphosphorylated Sodium Channel β1 Subunits Are Differentially Localized in Cardiac Myocytes

Abstract: Voltage-gated sodium channel ␣ and ␤ subunits expressed in mammalian heart are differentially localized to t-tubules and intercalated disks. Sodium channel ␤ subunits are multifunctional molecules that participate in channel modulation and cell adhesion. Reversible, receptor-mediated changes in ␤1 tyrosine phosphorylation modulate its ability to recruit and associate with ankyrin. The purpose of the present study was to test our hypothesis that tyrosine-phosphorylated ␤1 (pY␤1) and nonphosphorylated ␤1 subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 54 publications
6
135
0
Order By: Relevance
“…7C), and connexin-43 (Fig. 7C,6I, 6J) were localized to the intercalated disks, consistent with previous studies [11,23,29]. We found similar results in studies on acutely dissociated ventricular myocytes performed in parallel (not shown).…”
Section: Localization Of Sodium Channel α and β Subunitssupporting
confidence: 92%
See 2 more Smart Citations
“…7C), and connexin-43 (Fig. 7C,6I, 6J) were localized to the intercalated disks, consistent with previous studies [11,23,29]. We found similar results in studies on acutely dissociated ventricular myocytes performed in parallel (not shown).…”
Section: Localization Of Sodium Channel α and β Subunitssupporting
confidence: 92%
“…P17 male mice were anesthetized and perfused and isolated hearts or individual myocytes were prepared for immunocytochemistry as described [11]. Anti-Na v 1.5, anti-β3, anti-β4, anti-Na v 1.6, anti-β1 ex , anti-connexin-43, and anti-ankyrin B were applied at 1:100 dilution; anti-Ncadherin at 1:50; anti-Na v 1.…”
Section: Immunochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, sodium channel ␤ subunits may act indirectly through CAM homology domain-containing molecules. We have shown that ␤1 and N-cadherin interact in heart (41). Posttranslational modifications such as polysialylation have been shown to be important determinates in NCAM-mediated neurite outgrowth and neuronal fasciculation (4).…”
Section: Discussionmentioning
confidence: 94%
“…␤1 and ␤2 interact with tenascin-C and tenascin-R influencing cell migration, and participate in homophilic cell adhesion resulting in cellular aggregation and ankyrin recruitment (Srinivasan et al, 1998;Xiao et al, 1999;Malhotra et al, 2000Malhotra et al, , 2002. Furthermore, ␤1 interacts heterophilically with N-cadherin, contactin, neurofascin-155, neurofascin-186, NrCAM, and VGSC ␤2 (Kazarinova-Noyes et al, 2001;Malhotra et al, 2004;. Interactions between ␤1 and contactin, neurofascin-186, or ␤2 result in increased VGSC surface expression (Kazarinova-Noyes et al, 2001;.…”
Section: Introductionmentioning
confidence: 99%